CONTEXTUAL DISTANCE TEACHING TO IMPROVE TOURIST DRIVERS' ENGLISH LANGUAGE EXPRESSION - Wardana, I Ketut (Jurnal Santiaji Pendidikan (JSP), 2024)
This study aimed to assess the effectiveness of Contextual Distance Teaching (CDT) in improving driver’s English language expression and enhancing motivation, while also evaluating its significant influence on their English proficiency. Utilizing an action research approach conducted via the WhatsApp online platform, this study engaged 10 tourist drivers associated with the Bali Transport group, aged between 22 and 50. The study comprised two cycles, each consisting of three sessions. Data collection involved administering tests and questionnaires, including pretest, post-test 1, and post-test 2. Analysis was conducted using descriptive statistics and paired sample t-tests. The initial findings indicate that CDT effectively enhances the language expression of drivers in service-related contexts. The average pretest score, initially categorized as "poor" at 39, improved to 65 in post-test 1 and further increased to 75.8 in post-test 2, now categorized as "fair.", The main score of the questionnaire was 4.4 of 0-5 Likert scale implying the drivers had positive motivation and perception on the strategy apllied. The second statistic finding indicated a significant difference in the mean between the pre-test (Sig. and the post-test 1 (0.000 < 0.05) and post-test 2 (0.000 < 0.05). This study suggests that the implementation of CBT has a positive influence on reducing the number of language expression errors made by drivers as adult learners, leading to better English proficiency.